2009
DOI: 10.1002/bjs.6693
|View full text |Cite
|
Sign up to set email alerts
|

Effect of postoperative radiotherapy on autologous deep inferior epigastric perforator flap volume after immediate breast reconstruction

Abstract: In this study postoperative radiotherapy did not significantly affect breast volume after DIEP flap reconstruction. The potential need for postoperative radiotherapy should not deter women from undergoing immediate DIEP flap breast reconstruction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
55
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(58 citation statements)
references
References 17 publications
2
55
0
1
Order By: Relevance
“…Thus, the radiation eVect may have had a greater inXuence on the volume decrease in ALTF patients compared with PMMCF patients. However, the eVect of radiation on the Xap volume change remains controversial [14,15], and our univariate analysis result revealed that radiation did not signiWcantly aVect the volume change. Additionally, the pedicled Xap has been reported to have more tolerance to the radiation eVect on an entire Xap contracture to maintain its volume compared with the free Xap [16].…”
Section: Discussionmentioning
confidence: 98%
“…Thus, the radiation eVect may have had a greater inXuence on the volume decrease in ALTF patients compared with PMMCF patients. However, the eVect of radiation on the Xap volume change remains controversial [14,15], and our univariate analysis result revealed that radiation did not signiWcantly aVect the volume change. Additionally, the pedicled Xap has been reported to have more tolerance to the radiation eVect on an entire Xap contracture to maintain its volume compared with the free Xap [16].…”
Section: Discussionmentioning
confidence: 98%
“…Some studies evaluating immediate autologous tissue-based reconstruction before PMRT have reported reasonable rates of complications and satisfactory cosmetic outcomes. 6,29,30,38 However, overall complication rates are often imprecisely defined, as reported overall complications may include complications at both the donor and recipient sites. 39 Even overall complication rates for only the recipient site are not significantly affected by PMRT, especially since radiation therapy is not typically begun until 1 or 2 months after the transfer of the microvascular flap.…”
Section: Discussionmentioning
confidence: 99%
“…These surgeons have found the deleterious effects of PMRT to be acceptable and preferable to the delay in reconstruction and additional surgery required for the staged approach. 6,12,[26][27][28][29][30] Others have suggested that breast reconstruction with an MS FTRAM flap rather than a DIEP flap will avoid or decrease the deleterious effects of radiation because MS FTRAM flaps have a more robust blood supply. 31 However, it is not known whether irradiated MS FTRAM flaps experience less fat necrosis and fibrosis than irradiated DIEP flaps.…”
Section: Introductionmentioning
confidence: 99%
“…Radiotherapy after mastectomy but before reconstruction has not been shown to increase complications after autologous reconstruction (25); however, not all studies are in agreement (26,27). Certain studies show that postoperative radiotherapy to the breast reconstructed with a deep inferior epigastric perforator flap (DIEP) or transverse rectus abdominis myocutaneous (TRAM) flap has no effect on the reconstruction (28,29), while several others show a considerable negative effect on the final results of autologous reconstruction (24,26,(30)(31)(32)(33)(34).…”
Section: The Effect Of Radiotherapy On Breast Reconstructionmentioning
confidence: 99%